Beautiful Timeless Art: Kalamkari Painting - Rani, Archana (Journal of Commerce and Trade, 2021)
Kalamkari painting is a beautiful art form of Andhra Pradesh. Kalamkari is a type of hand-painted or block-printed cotton textile. It is more than just being a fabric used for clothing or home. It is more than textiles to an experience that culture has witnessed over centuries. This textile is supposed to be a multi-colored fabric in one of its rarest forms. Kalamkari is known to be a healing fabric, as the colours, motifs and the narration of magical forms create an aura that heals an individual physically and spiritually. Only natural dyes are used in Kalamkari, which is an ancient style of hand painting done on cotton or silk fabric with a tamarind pen. Today a stylish range of home décor products made with Kalamkari is available, namely, wall hangings, bedcovers, cushion covers, even rugs and theater backdrops, besides beautiful saris, dress materials, and stoles. The research paper is of exploratory nature. there are a very few literatures available on the history and evolution of kalamkari, there is very little information available on the current situation. Thus, the exploratory method was chosen to write the timeless beauty of traditional painting kalamkari. This research paper was started with the style, colours and techniques with the idea of bringing about innovation in Todays Kalamkari. Classification-JEL : Z11, Z19